POLITIK HUKUM KEWARGANEGARAAN INDONESIA DALAM MENJAMIN HAK KEWARGANEGARAAN PEREMPUAN - Amalia Diamantina (Faculty of Law, Universitas Diponegoro, 2014)
Indonesian legal political of citizenship is directed to give an equal act for all of citizen. The protection of women's citizenship rights are arranged so that women can give her citizenship to her children. However, there are still shortcomings in the arrangement and the implementation of the protection of the right of citizenship of women.